Lysine-specific demethylase 2A expression is associated with cell growth and cyclin D1 expression in colorectal adenocarcinoma. Issue 4 (November 2018) - Cao, Lin-Lin; Du, Changzheng; Liu, Hangqi; Pei, Lin; Qin, Li; Jia, Mei; Wang, Hui
Objective: Lysine-specific demethylase 2A (KDM2A), a specific H3K36me1/2 demethylase, has been reported to be closely associated with several types of cancer. In this study, we aimed to investigate the expression and function of KDM2A in colorectal adenocarcinoma. Methods: A total of 215 colorectal adenocarcinoma specimens were collected, and then subjected to immunohistochemistry assay to evaluate the expression levels of KDM2A, cyclin D1 and other proteins in colorectal adenocarcinoma tissues. Real-time polymerase chain reaction, Western blot, and other molecular biology methods were used to explore the role of KDM2A in colorectal adenocarcinoma cells. Results: In this study, we report that the expression level of KDM2A is high in colorectal adenocarcinoma tissues, and this high expression promotes the proliferation and colony formation of colorectal adenocarcinoma cells, as demonstrated by KDM2A knockdown experiments. In addition, the expression of KDM2A is closely associated with cyclin D1 expression in colorectal adenocarcinoma tissues and cell lines. Conclusions: Our study reveals a novel role for high-expressed KDM2A in colorectal adenocarcinoma cell growth, and that the expression of KDM2A is associated with that of cyclin D1 in colorectal adenocarcinoma.